1988
DOI: 10.1207/s15327752jpa5201_9
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Millon Clinical Multiaxial Inventory in the Assessment of Affective Disorders

Abstract: The Millon Clinical Multiaxial Inventory (MCMI) was administered to 270 adult outpatients with major affective disorders at the same time that a semistructured, diagnostic interview was conducted by a clinician. The mood of the patient was then rated, and the clinician completed the Hamilton Depression Rating Scale and the Mania Rating Scale. A consensual diagnosis was arrived at by the team of investigators using DSM-III criteria. Significant correlations were found between four MCMI affective scales and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…One questionnaire that corresponds with DSM personality disorders is the Millon Clinical Multiaxial Inventory (MCMI-II). This self-report questionnaire consists of 20 clinical scales grouped into pathological personality groups and clinical syndromes (Millon, 1982;Choca et al, 1988). However, each scale is measured along a standardized dimensional spectrum not only to assess severity, but more importantly to enable comparison between scales.…”
Section: Introductionmentioning
confidence: 99%
“…One questionnaire that corresponds with DSM personality disorders is the Millon Clinical Multiaxial Inventory (MCMI-II). This self-report questionnaire consists of 20 clinical scales grouped into pathological personality groups and clinical syndromes (Millon, 1982;Choca et al, 1988). However, each scale is measured along a standardized dimensional spectrum not only to assess severity, but more importantly to enable comparison between scales.…”
Section: Introductionmentioning
confidence: 99%
“…Scale N has been found to converge highly with comparable measures of hypomanic and manic symptoms such as the Minnesota Multiphasic Personality Inventory Manic Scale (r 5 .66) and the Minnesota Multiphasic Personality Inventory-Wiggins Hypomania Scale (r 5 .67), and correctly classifies respondents over 93% of the time when base rate (BR) scores are equal to or exceed the clinical cut-off score of 75 (Millon, 1983). Choca et al (1988) additionally reported a moderate correlation with the Young Mania Rating Scale (r 5 .36) and a 56% accurate identification of bipolar patients. National Institute for Mental Health Diagnostic Interview Schedule (DIS; Regier et al, 1984).…”
Section: Methodsmentioning
confidence: 97%
“…Clinical experience with the MCMI indicates that one or more elevations above a baserate score (BR) of 74 on scales for Psychotic Thinking, Psychotic (major) Depression, or Paranoid Thinking or above BR 84 on scales for Anxiety, Somatization, Hypomania, Dysthymia, Alcohol Abuse, or Drug Abuse identifies patients for whom further evaluation should be considered. Choca, Bresolin, Okonek, and Ostrow (1988) found that the Dysthymia scale is a better indicator of major depression than the Psychotic Depression scale.…”
Section: Subjectsmentioning
confidence: 98%